Emotion in posttraumatic stress disorder : etiology assessment, neurobiology and treatment - Tull, Matthew T.; Kimbrel, Nathan A. (Academic Press, 2020)
"Emotion in Posttraumatic Stress Disorder provides an up-to-date review of the empirical research on the relevance of emotions, such as fear, anxiety, shame, guilt, and disgust to posttraumatic stress disorder (PTSD). It also covers emerging research on the psychophysiology and neurobiological underpinnings of emotion in PTSD, as well as the role of emotion in the behavioral, cognitive, and affective difficulties experienced by individuals with PTSD. It concludes with a review of evidence-based treatment approaches for PTSD and their ability to mitigate emotion dysfunction in PTSD, including prolonged exposure, cognitive processing therapy, and acceptance-based behavioral therapy."--Publisher's website